Desorption isotherms of acerola fruits variety ’Okinawa’ - Reis, Daíse Souza; Neto, Acácio Figueiredo; Costa, Josenara Daiane de Souza; Almeida, Francisco de Assis Cardoso; Gouveia, Josivanda Palmeira Gomes (Científica, 2017)
The cultivation of acerola in Brazil is growing. The acerola fruit is known to have several properties concurrent with where it is grown. The determination of the water activity of biological products becomes essential in studies on drying, storage and packaging processes since the higher the water activity of a product, the higher the susceptibility to attacks by microorganisms. This study aimed to evaluate desorption isotherms of acerola fruits (Malpighia glabra L.) for the temperatures 30, 40 and 50 °C by the indirect static method. The experimental data were adjusted to the mathematical models BET, GAB, Halsey, and Oswin and Smith. Analyses of residues, coefficient of determination, relative standard deviation and estimated standard deviation were calculated for each adjusted model and used to evaluate the model that best adjusted to desorption isotherms. Based on the results obtained, the Smith’s model represented isotherms with a higher precision for this variety of acerola.